An extreme climate transition in the Caribbean's Virgin Islands. II. Sun and Northern hemisphere atmospheric–oceanic feedbacks - N. Brice Orange; Noah Stolz; Molly Ryan; David L. Chesny; Bruce Gendre; Avram G. Primack; Timothy W. Giblin; David C. Morris (International Journal of Climatology, 2020)
The last 60 years of extreme climate variability, and a 1980s climatic shift in the Caribbean's Virgin Islands were analysed to explore relationships with the Atlantic Multidecadal Oscillation (AMO), North Atlantic Oscillation (NAO), El‐Niño Southern Oscillation (ENSO), and sunspot numbers. AMO, NAO, ENSO, and sunspot number relationships with the Virgin Islands climate were assessed from measures to their number density of statistically significant correlation with 17 extreme climate indices. Decadal daytime cooling negatively (positively) correlated with AMO (ENSO) records, while moderate nightly warming positively related to the AMO, ENSO, and NAO. In the decades following the late 1970s to early 1980s, evidence was suggestive of an increased lead time for local temperature responses. A relationship with sunspots in extreme temperature was indicated in daytime variations, at a lead time consistent with NAO influences expected from solar activity. The NAO, and to a lesser extent the ENSO, exhibited a negative association to extreme precipitation, while the AMO and sunspot number records only supported a connectivity post 1970s. Twentieth century strengthening of the tropical Atlantic tripole in sea surface temperatures is implicated as the source of decadal warming, and an increasingly rainy climate. More frequent poleward shifts of the Atlantic Intertropical Convergence Zone are suggested to explain recent decadal rises in intense rainfall events, from increased occurrences in organized deep convection.

An extreme climate transition in the Caribbean's Virgin Islands. I. Evidence of teleconnection with the 1976/1977 Pacific climate shift - N. Brice Orange; David L. Chesny; Avram G. Primack; Bruce Gendre; Sandra N. Maina; Timothy W. Giblin; David C. Morris (International Journal of Climatology, 2018)
We present the Caribbean's Virgin Islands’ climate variability over the last 60 years from indices of extreme temperature and precipitation, as well as their quantitative support for a recent climatic shift (1983.2 ± 5.5 years). The region's climate indices (defined via time series averages) and trends (defined via linear least squares regression fitting) of extreme temperature and precipitation were cross‐examined from 1952, 1961, 1978, and 1983–2014 to diagnose: the area's climatic extremes; a climatic transition's role in assessing decadal climate anomaly rates; and to provide an analytically independent test of the transition's existence. Analyses relied on the use of varying physical constraints to include weighting from statistical and non‐statistical uncertainties in our climatic outcomes. We report that diurnal warming and enhanced precipitation accompanied each interval, however, non‐negligible deviations existed in comparisons between the same anomalies in any 2 intervals. Our Virgin Islands’ long (1952, 1961–2014) versus short (1978, 1983–2014) climate variation comparisons provide evidence for the manifestation of decadal (or longer) shifts, and thus, biases, in recent Caribbean reports. Our climatic transition's overlap with the renowned 1976/1977 Pacific event insinuates a local Caribbean teleconnection, and contributes to the evidence growing globally for 1980s’ shifts in an abundance of feedback measures of Earth's energy budget.

Extreme passive acoustic telemetry detection variability on a mesophotic coral reef, United States Virgin Islands - Jonathan Jossart; Richard S. Nemeth; Avram Primack; Robert Stolz (Marine Biology, 2017)